EP694 The role of pulmonary metastectomy in gynaecology malignancy. (1st November 2019) - Armstrong, F; Brien, OO; Walsh, T; Mc Vey, R; Boyd, W; Eaton, D; Healy, D; Redmond, K; Brennan, D
Abstract : Introduction/Background: Long term outcomes after pulmonary metastectomy for recurrent gynaecology malignancy are not well documented. We sought to examine the indications and outcomes of patients who had a pulmonary metastectomy for gynaecology malignancy in a tertiary referral centre in Dublin Ireland. Methodology: A retrospective analysis of medical records for the period 01/01/2014 to 01/01/2019 was performed. Search criteria included history of primary gynaecological malignancy, metastectomy, Video assisted thoracic surgery (VATS), thoracotomy and wedge resection. Results: A total of 10 patients underwent pulmonary metastectomy for isolated recurrent disease. Median age was 65 yrs (Range 45–85 yrs). Primary diagnosis were ovarian cancer (n=5), uterine sarcoma (n=4) and mucinous adenocarcinoma of the cervix (n=1). The most common procedure was VATS assisted wedge resection (n=8). 37.5% (3/8) also requiring pleurodesis. The other procedures documented are VATS assisted excision of epicaridial lymph node (n=1) and a small anterior thoracotomy (n=1). The time to pulmonary recurrence was 3.6 years (Range 1 yr to 17 yrs). Histology confirmed recurrence in all cases. Two patients were lost to follow up. Of the remaining 8 patients the mean time to disease progression was 8.8 months (Range 4–24 months) following metastectomy. There were no grade III morbidities in this cohort. With regards to ovarian carcinoma 40% (2/5) have stable disease following disease progression with 1 patient currently receiving chemotherapy and 1 patient on a PARP inhibitor. Two ovarian cancer patient s died 5 months and 2 years following metastectomy and 1 patient was lost to follow up. Three of the uterine sarcoma patients remain under surveillance, 2 with disease progression. Conclusion: Pulmonary metastectomy for recurrent gynaecological cancer is an acceptable and safe form of treatment in carefully selected patients. Patients with isolated pulmonary recurrences should be considered for surgical intervention if their performance status is suitable. Disclosure: Nothing to disclose.